Performance Analysis of Handoff in CDMA Cellular System (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Handoff mechanism is extremely important in cellular network because of the cellular architecture employed to maximize spectrum utilization. This unique feature has driven the rapid growth in the mobile network industry, changing it from a new technology into a massive industry within less than two decades. Handoff is the essential functionality for dealing with the mobility of the mobile users. This paper shows the soft handoff effects on the uplink direction of IS-95 CDMA networks is carried out, leading to optimize soft handoff for capacity under perfect power control approach. In practical systems, there is a nonzero handoff completion delay and soft handoff provides the required robustness to delays, although it comes at the expense of additional network resources. Thus, there is a tradeoff between the extent of soft handoff required and the handoff execution delay. This paper presents an analytical framework to study this tradeoff and also discuss simulation results simulated with the help of Matlab. For this, handoff dropping probability is minimized up to 0.1%.